Pengaruh Latihan Kecepatan Terhadap Keterampilan Dribbling Permainan Futsal Peserta Ekstrakurikuler di SMAN 1 Lempuing Jaya - Diatmaja, Kadek Cakya; Riyoko, Endie; Manullang, Jujur Gumawan (Institut Teknologi Pendidikan Indonesia, 2023)
The aims of the research were to find out whether there was speed training in improving futsaldribbling abilities and to find out whether there were differences in speed training and otherexercises in terms of increasing futsal dribbling skills in extracurricular activities at SMA Negeri 1Lempuing Jaya. The sample in this study that will be used as a sample is futsal extracurricularstudents from SMA Negeri 1 Lempuing Jaya with a total of 20 students. The data collection wascarried out using student worksheets in the form of pretest and posttest. The research conducted atSMA Negeri 1 Lempuing Jaya involving as many as 20 futsal extracurricular students produceddata including the initial test data, the smallest data obtained was 20.14 seconds and the largestdata was 29.88 seconds with an average of 22.28 seconds. There was a change in the final testdata after being given treatment in the form of speed training for 16 meetings of the trainingprogram guide (attached). The smallest data was 20.08 seconds and the largest data was 29.73seconds with an average of 22.14 seconds. The results of the hypothesis testing showed that there was an effect of speed training on the dribbling ability of futsal extracurricular students at SMA Negeri 1 Lempuing Jaya because the Sig value was > 0.05. The results of the research show data analysis and research hypothesis testing, this study can be concluded that there is an effect ofspeed training on the dribbling abilities of futsal extracurricular students at SMA Negeri 1Lempuing because the sig value is 0.501> 0.05.